2010
DOI: 10.1371/journal.pntd.0000643
|View full text |Cite
|
Sign up to set email alerts
|

First Description of a Cluster of Acute/Subacute Paracoccidioidomycosis Cases and Its Association with a Climatic Anomaly

Abstract: BackgroundIdentifying clusters of acute paracoccidioidomycosis cases could potentially help in identifying the environmental factors that influence the incidence of this mycosis. However, unlike other endemic mycoses, there are no published reports of clusters of paracoccidioidomycosis.Methodology/Principal FindingsA retrospective cluster detection test was applied to verify if an excess of acute form (AF) paracoccidioidomycosis cases in time and/or space occurred in Botucatu, an endemic area in São Paulo Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 12 publications
3
50
0
6
Order By: Relevance
“…In Brazil, ecological correlates obtained through spatial analyses indicate that moisture availability plays an important role in PCM distribution (9). This methodology recently revealed the existence of a cluster of acute/subacute cases potentially linked to a climatic anomaly caused by the 1982-1983 El Niño Southern Oscillation phenomenon (8).…”
Section: Overview Of the Limited Geographic Distribution Of The Mycosismentioning
confidence: 95%
“…In Brazil, ecological correlates obtained through spatial analyses indicate that moisture availability plays an important role in PCM distribution (9). This methodology recently revealed the existence of a cluster of acute/subacute cases potentially linked to a climatic anomaly caused by the 1982-1983 El Niño Southern Oscillation phenomenon (8).…”
Section: Overview Of the Limited Geographic Distribution Of The Mycosismentioning
confidence: 95%
“…Recently, Arantes and others 27 reported environmental nucleic acid sequences belonging to P. lutzii in the hyperendemic region of Botucatu in the southeast region of Brazil, 27 an area formerly assumed to have a high prevalence of species S1. [2][3][4] However, no increase in clinical cases of PCM caused by P. lutzii has been seen in areas others than the central-west region of Brazil, which could be related to differences in the survival and growth of this species in nature, differences in human exposure, or even host resistance to infection in this area, and the misidentification of this pathogenic species by currently available techniques.…”
mentioning
confidence: 99%
“…Prevention of human exposure to P. brasiliensis may be achieved if their survival and growth conditions are known, which can be possible by studying the geographical distribution of PCM (30). Studies have reported only the morphology of the different species, and the different levels of compromise that each species causes still need to be determined (31).…”
Section: Discussionmentioning
confidence: 99%